Systematic screening of 96 Schistosoma mansoni cell-surface and secreted antigens does not identify any strongly protective vaccine candidates in a mouse model of infection - Crosnier, Cecile (Wellcome Open Res, 2019)
Background: Schistosomiasis is a major parasitic disease affecting people living in tropical and sup-tropical areas. Transmission of the parasite has been reported in 78 countries, causing significant morbidity and around 200,000 deaths per year in endemic regions. The disease is currently managed by the mass-administration of praziquantel to populations at risk of infection; however, the reliance on a single drug raises the prospect of parasite resistance to the only treatment widely available. The development of an effective vaccine would be a more powerful method of control, but none currently exists and the identification of new immunogens that can elicit protective immune responses therefore remains a priority. Because of the complex nature of the parasite life cycle, identification of new vaccine candidates has mostly relied on the use of animal models and on a limited set of recombinant proteins. Methods: In this study, we have established an infrastructure for testing a large number of vaccine candidates in mice and used it to screen 96 cell-surface and secreted recombinant proteins from Schistosoma mansoni. This approach, using standardised immunisation and percutaneous infection protocols, allowed us to compare an extensive set of antigens in a systematic manner. Results: Although some vaccine candidates were associated with a statistically significant reduction in the number of eggs in the initial screens, these observations could not be repeated in subsequent challenges and none of the proteins studied were associated with a strongly protective effect against infection. Conclusions: Although no antigens individually induced reproducible and strongly protective effects using our vaccination regime, we have established the experimental infrastructures to facilitate large-scale systematic subunit vaccine testing for schistosomiasis in a murine infection model.